(untitled) (mathematica didactica, 2025)
Effective civic engagement in democratic societies requires active participation and a broad understanding of data and statistics on societal issues. However, statistics and data science education in schools and universities is often neither designed to teach relevant skills nor to improve students’ statistical literacy. As an extension of statistical literacy, this paper introduces the sub-discipline of civic statistics. Civic statistics focuses on understanding and engaging with statistical information on societal issues as provided by the media, statistical offices, non-governmental organizations and other statistical providers. In this article, we present examples of possible application scenarios for teacher training and derive implications for the thematization of civic statistics in the context of teacher training.